Trauma, Justice, and Equity: Using Critical Theories and Concepts to Address Systemic Harm Among Youth Punishment System-Involved Black Girls - Camille R. Quinn (Behavioral Sciences)
This review critically evaluates the existing literature on youth punishment system (YPS)-involved Black girls and their intersections of with trauma and post-traumatic stress disorder (PTSD). It synthesizes findings from previous studies, identifying key research trends, gaps, and controversies, while also highlighting areas in need of further investigation. Black girls, particularly those involved in systems such as juvenile justice, child welfare, and education, often face disproportionate exposure to violence, abuse and neglect, trauma, and systemic racism. For Black girls with histories of trauma and PTSD, these intersecting challenges are compounded by the added vulnerabilities of race, gender, and YPS involvement. This article argues that addressing the complex needs of this population requires recognition that Black girls’ harm is criminalized and, therefore, inextricably linked to their YPS-involvement, so a comprehensive, culturally responsive approach that includes trauma-informed care, healing-centered engagement, and holistic support systems are needed. Equitable access to tailored mental health services, educational resources, and culturally relevant interventions is essential to mitigate the long-term effects of trauma, promote resilience, and foster healing. Additionally, advocacy efforts to dismantle systemic harm and address racial and gender disparities are critical for creating inclusive environments that empower and support Black girls in these systems. By centering their lived experiences, this review emphasizes the importance of fostering environments of healing, justice, and equity for this vulnerable population.